2013
DOI: 10.1002/chir.22130
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Discrimination by Vibrational Spectroscopy Utilizing Local Modes

Abstract: Chiral discrimination of homochiral and heterochiral H-bonded complexes is a challenge for both experimentalists and computational chemists. It is demonstrated that a two-pronged approach based on far-infrared vibrational spectroscopy and the calculation of local mode frequencies facilitates the chiral discrimination of H-bonded dimers. The local H-bond stretching frequencies identify the strongest H-bonds and by this the dominating chiral diastereomer. This is shown in the case of peroxide, trioxide, hydrazin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 81 publications
(162 reference statements)
0
23
0
Order By: Relevance
“…It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments . Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, NN bonds, NF bonds, CO bonds, and CX (X=F, Cl, Br, I) bonds, and weak chemical interactions such as: hydrogen bonding, halogen bonding, pnicogen bonding, chalcogen bonding, tetrel bonding, and recently BH···π interactions …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments . Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, NN bonds, NF bonds, CO bonds, and CX (X=F, Cl, Br, I) bonds, and weak chemical interactions such as: hydrogen bonding, halogen bonding, pnicogen bonding, chalcogen bonding, tetrel bonding, and recently BH···π interactions …”
Section: Introductionmentioning
confidence: 99%
“…[25,[73][74][75] It has been shown that the local stretching force constant k a is a superior bond strength measure compared to the often used bond dissociation energies (BDE) and bond dissociation enthalpies (BDH) as they contain cumulative effects of geometry relaxation, multiple bonding interactions, and also electronic density reorganizations of the dissociated fragments. [73,76,77] Local stretching force constants k a have been successfully used to determine the intrinsic bond strength of covalent bonds such as: CC bonds, [74,75,78,79] NN bonds, [80] NF bonds, [81] CO bonds, [82] and CX (X = F, Cl, Br, I) bonds, [83][84][85][86] and weak chemical interactions such as: hydrogen bonding, [87][88][89][90] halogen bonding, [91][92][93] pnicogen bonding, [94][95][96] chalcogen bonding, [73,77] tetrel bonding, [97] and recently BH � � � p interactions. [16,17] The main objectives of this paper are: (i) to evaluate the nature of the BÀ B, BÀ H b , and BÀ H t bonds; (ii) to evaluate why intermediate species may or may not facilitate the reversibility reactions in the perspective of thermodynamics and intrinsic bond strength; (iii) to provide a new tool to characterize new (potential) intermediates and their role for the reversibility of the hydrogenation/dehydrogenation reactions; and (iv) to give guidelines whether intermediates may be stable enough to be isolated.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] This approach is especially attractive when applied to H-bonded complexes [24] and when measured vibrational frequencies, rather than calculated vibrational frequencies, are available. [25,26] In this work, we will extend the description of molecular properties based on measured vibrational frequencies to determine the vibrational properties of isotopomers of a given target molecule.…”
Section: Introductionmentioning
confidence: 99%
“…One has however to keep in mind that systems deprived of very floppy or anharmonic motions, like those made of rigid subunits or involving a dominant electrostatic interaction, are very satisfactorily described in terms of harmonic frequencies of the most stable isomers [184]. Last, attempts at assessing the chiral discrimination effects in terms of local mode description have been proposed but not applied to experimentally studied systems yet [185].…”
Section: Vibrational Frequencies Calculationsmentioning
confidence: 98%